2018
DOI: 10.1186/s12864-018-4775-x
|View full text |Cite
|
Sign up to set email alerts
|

TSVdb: a web-tool for TCGA splicing variants analysis

Abstract: BackgroundCollaborative projects such as The Cancer Genome Atlas (TCGA) have generated various -omics and clinical data on cancer. Many computational tools have been developed to facilitate the study of the molecular characterization of tumors using data from the TCGA. Alternative splicing of a gene produces splicing variants, and accumulating evidence has revealed its essential role in cancer-related processes, implying the urgent need to discover tumor-specific isoforms and uncover their potential functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 21 publications
(19 reference statements)
0
83
0
Order By: Relevance
“…We searched all the 9 genes identified in this study (CLK1, COL6A3, CD44, ARHGEF9, HKDC1, CHEK1, HNF4A, SERPINA1, CALD1) against TSVdb and downloaded the junction usage value for colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ). Junction usage is calculated by dividing junction quantification value to mean junction quantification value of that person for a specific gene [39]. We combined junction usage for 379 primary solid tumor samples with 1 , consistent with what we observed in the two GEO datasets.…”
Section: Validation Of Splicing Events Using Tcga Datamentioning
confidence: 65%
“…We searched all the 9 genes identified in this study (CLK1, COL6A3, CD44, ARHGEF9, HKDC1, CHEK1, HNF4A, SERPINA1, CALD1) against TSVdb and downloaded the junction usage value for colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ). Junction usage is calculated by dividing junction quantification value to mean junction quantification value of that person for a specific gene [39]. We combined junction usage for 379 primary solid tumor samples with 1 , consistent with what we observed in the two GEO datasets.…”
Section: Validation Of Splicing Events Using Tcga Datamentioning
confidence: 65%
“…All patient overall survival (OS) data and junction usage data were downloaded from TSVdb [27]. All patients with OS data were separated into two groups based on the median value of a particular junction usage.…”
Section: Survival Analysismentioning
confidence: 99%
“…To validate the splicing events identified in this study in an independent dataset, we used a recently developed tool TSVdb [27], which integrates and visualizes alternative splicing data based on TCGA samples for 33 tumor types. We searched all the 10 genes identified in this study (CLK1, COL6A3, CD44, ARHGEF9, HKDC1, CHEK1, HNF4A, SERPINA1, CALD1, FBLN2) against TSVdb and downloaded the junction usage value for colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ).…”
Section: Validation Of Splicing Events Using Tcga Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to both volume and complexity of the data as well as availability only in matrix 45 form, users without bioinformatic expertise may find it challenging to explore this resource. A number of previous studies have shown that interactive webtools enable easy exploration of large and complex molecular data sets (Sun et al, 2018;Dumas et al, 2016;Ono et al, 2017). Therefore, we developed the user-friendly, interactive MetaMap webtool.…”
Section: Introductionmentioning
confidence: 99%